Investigating the structural, thermal, and electrical properties of PVDF/PMMA blends reinforced with GNP, MXene, and GNP-MXene hybrids - Nitesh Kumar Nath; Rajanikanta Parida; Bichitra Nanda Parida; Nimai Charan Nayak (Discover Applied Sciences)
Abstract The structural, thermal, and electrical properties of graphene nanoplatelets (GNPs), MXene (Ti3C2Tx), and GNP-MXene hybrids (GMHs) incorporated into a polymer blend matrix were comprehensively investigated in this study. Composite films were fabricated using the solution casting method and subjected to systematic characterization. Among the samples, the GMH-based composites exhibited the highest β-phase content (62.5%), as confirmed by structural analyses that also revealed notable variations in crystallinity. Surface morphological analysis indicated uniform filler dispersion and enhanced interfacial interactions within the polymer matrix. Thermal analysis demonstrated that the presence of GMHs significantly influenced the melting behavior and overall crystallinity of the composites. Dielectric spectroscopy further revealed that the hybrid nanofillers enhanced electrical conductivity and facilitated efficient charge transport. Notably, the composite containing 5 wt% GMHs achieved a high dielectric permittivity of 101.9 at 100 Hz and an AC conductivity of 1.07 × 10−4 S/m. The hybrid system maintained stable dielectric performance over a wide frequency and temperature range. Additionally, dielectric measurements indicated deviation from classical Debye-type relaxation behavior, suggesting complex polarization dynamics. Overall, these results highlight the synergistic effects of hybrid fillers on the microstructure and functional performance of polymer blends, offering valuable insights for the design of high-performance dielectric materials for electronic applications.